Understanding Platelet-Rich Plasma as Potential Therapy To Improve Cardiac Function After Myocardial Infarction: Based On Evidence - Linda Chiuman; Dearni Anggita Krismayani Purba; Hendy Million Samin (Faculty of Medicine, Universitas Diponegoro, 2023)
Myocardial infarction is the leading cause of death in the world’s population. The sudden and progressive loss of cardiomyocyte contractile cells due to infarction is disproportionate to the number of new cells formation. This pathological condition will ultimately reduce the function of the heart muscles. Platelet-rich plasma (PRP) in the last decade has been attracting attention regarding its role in cell regeneration. The content of cytokines and growth factors contained in PRP such as Platelet-Derived Growth Factor (PDGF), Transforming Growth Factor Beta 1 (TGF-Β1), Epidermal Growth Factor (EGF), Vascular Endothelial Growth Factor (VEGF), Basic Fibroblast Growth Factor (bFGF) and others are known to be involved in the migration, proliferation, and differentiation of various cell types and to induce post-ischemic angiogenesis. This review aims to analyze and investigate the benefits of PRP therapy in myocardial infarction. Recent literatures regarding the use of PRP in myocardial infarction was collected by searching PubMed and Google Scholar databases with the keywords of “Platelet-rich plasma”, “Myocardial Infarction”, “Reperfusion”, and “Angiogenesis”. The researches used was published between January 2011 and December 2022. Based on the results, Platelet-rich Plasma (PRP) is considered capable of accelerating angiogenesis, mitogenesis, protect cells from free radicals, reduce infarct area and scar tissue in myocardial infarction. PRP can also improve cardiac function in post myocardial infarction by increasing ejection fraction. In addition, PRP can also reduce treatment costs due to the risk of myocardial infarction complications such as bleeding and infection.